Liquidity Analysis Of Chandigarh Transport Undertaking (CTU) - Aggarwal, Deepika; Singh, Baldeep (Gyan Management Journal, 2019)
Transport plays a vital role in overall growth of the economy. It helps in promoting the development and serves as a motor in accelerating the progress of the nation. Road transport is the basic and important requirement for the movement of people as well as goods. Anefficient and organized road network hastens the economic advancement of the country which serves as a strong industrial base for the success of whole economy. Bus transport service is basically provided by STUs. In Chandigarh bus transport is provided by Chandigarh Transport Undertaking (CTU). This study is confined to the liquidity analysis of Chandigarh Transport Undertaking (CTU) concluded with findings and suggestions.
Keywords: Working capital; trend; components; ratio